RTSP-based Mobile Peer-to-Peer Streaming System - Jani Peltotalo; Jarmo Harju; Lassi Väätämöinen; Imed Bouazizi; Igor D. D. Curcio (International Journal of Digital Multimedia Broadcasting)
Peer-to-peer is emerging as a potentially disruptive technology for content distribution in the mobile Internet. In addition to the already well-known peer-to-peer file sharing, real-time peer-to-peer streaming is gaining popularity. This paper presents an effective real-time peer-to-peer streaming system for the mobile environment. The basis for the system is a scalable overlay network which groups peer into clusters according to their proximity using RTT values between peers as a criteria for the cluster selection. The actual media delivery in the system is implemented using the partial RTP stream concept: the original RTP sessions related to a media delivery are split into a number of so-called partial streams according to a predefined set of parameters in such a way that it allows low-complexity reassembly of the original media session in real-time at the receiving end. Partial streams also help in utilizing the upload capacity with finer granularity than just per one original stream. This is beneficial in mobile environments where bandwidth can be scarce.